REPRESENTASI PROSES PENERIMAAN DIRI TOKOH UTAMA DALAM DRAMA KOREA TRUE BEAUTY: ANALISIS PSIKOLOGI SASTRA MASLOWIAN - Istianah, Uut; Fatoni, Akhmad; Hermawan, Wawan (Universitas Wiralodra, 2025)
Drama Korea